(untitled) (International Seven Journal of Health Research, 2024)
CAR-T and CAR-NK cells are immune system cells modified in the laboratory to express a chimeric antigen receptor, which allows them to recognize and specifically attack cancer cells, achieving efficacy in the treatment of certain types of cancer, especially hematological cancers. The aim of this systematic review is to report on the use of treatment using CAR-T and CAR-NK cells, their pros and cons, describe their handling process and their application in patients. The methodology of this study is a systematic review using the MEDLINE, PubMed and CAPES databases to search for articles on CAR-T and CAR-NK cells, published between 2020 and 2022, using the keywords car-t cells and immunotherapy and neoplasm and chimeric antigen receptors and natural killer cells or car-t cell and immunotherapy and neoplasm and chimeric antigen receptors and natural killer cell. The main results were 463 reports. Of these, 12 met the eligibility criteria and were included in the study. They addressed the differences between CAR-T and CAR-NK, their advantages and disadvantages, the CAR manufacturing process, limitations of the two therapies, their manufacture and application in patients. It was concluded that CAR-NK cell therapy has been shown to have fewer adverse effects, to have a wide option for collection and to be more easily manipulated compared to CAR-T cells.